Cavendish: The Experimental Life - Christa Jungnickel (Studies 7: Max Planck Research Library in the History and Development of Knowledge, 2016)
Two gifted eighteenth-century Londoners, Charles Cavendish and his painfully preeminent son Henry were descendants of paired revolutions, one political and one scientific. Scions of a powerful revolutionary family, they gave an original turn to the duty of public service that attached to their social rank. The English aristocracy knew one of its finest hours when Henry Cavendish gently laid his delicate weights in the scales of the first great precision balance of the century. For this action to happen, it took two generations and two kinds of invention, one in social forms and the other in scientific methods. This joint biography of father and son tells how it came to pass. Henry Cavendish is best known for his researches in chemistry, electricity, and heat, but in truth he worked in every part of physical science, bringing to it his unique combination of experimental precision and mathematical penetration. His accomplishment is likened to the highest example: since the death of Newton, Humphry Davy wrote, England has suffered "no scientific loss so great as that of Cavendish." Through inheritance he became immensely rich. Regarding intellect and fortune, he is called "the wisest of the rich and the richest of the wise." In his exclusive devotion to science, he is compared with "the most austere anchorites," who were "not more faithful to their vows." With reference to his legendary shyness, he is described as a man of "most reserved disposition," of a "degree bordering on disease." He was, to be sure, all of these things: one of the best scientists of his time, one of the richest men in the kingdom, a member of one of the politically most influential aristocratic families, a scientific fanatic, and a person of extraordinary peculiarities. This biography, a major revision of the original published in 1999, offers an enlarged understanding of the eighteenth century world of science and a reevaluation both of the scientific genius and of the remarkable personality of Henry Cavendish. It is a comprehensive study of science, family, and society in the eighteenth century.